The effectiveness of TikTok content creators in translating Generation Z purchase behavior toward sales of beauty products in Tacloban City - Abdullah, Saimah A.; Legaspi, Alexamae M.; Secillano, Jo Dinella M.; Lorenzo, Anida Bernadette B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2025)
Tik Tok has become one of the most influential platforms among Gen Z and a vital tool for digital marketing. With features like short-form videos, viral challenges, and influencer content, it enables content creators to shape consumer choices. However, the effectiveness of these creators in turning purchase intent into actual sales remains uncertain. This study explored how Tik Tok content creators influenced Generation 2's purchase behavior toward beauty products in Tacloban City. It examined creator characteristics-attractiveness, expertise, and trustworthiness-and content strategies such as content types, audience interaction, and calls-to-action. Data were gathered from 401 active Gen Z TikTok users through a structured survey. Results showed that while attractiveness drew initial attention, trustworthiness and expertise more strongly predicted engagement and purchase intent. Authentic product reviews, relatable tutorials, and interactive live sessions built trust and influenced purchasing. Clear calls-to-action and strategic content approaches increased purchase intent. Multiple regression analysis confirmed that content types, interaction, and calls-to-action significantly influenced Gen Z's buying decisions. The study concluded that Gen Z responds to creators who offer authentic, expert-driven content with interactive engagement. Barriers like complex checkout processes, entertainment-focused use, and market competition hindered actual purchases. Overall, the findings highlight the importance of authenticity, credibility, and strategy in shaping consumer behavior on Tik Tok's beauty market.
Undergraduate thesis (Bachelor of Science in Management) -- University of the Philippines, Tacloban.
Includes bibliographical references.
Keywords: Social media marketing -- Tacloban City; Tiktok; Content creator; Influencer marketing; Purchase behavior; Beauty products